Gender and Age Factors in Subjective Wellbeing and Quality of Life Among College Students - Kurnia, Ayu; Kaloeti, Dian Veronika Sakti; Yuniarti, Kwartarini Wahyu; Siswandi, Ahmad Gimmy Prathama; Remila, Josetta Maria (Faculty of Psychology, Diponegoro University, 2021)
Quality of life (QOL) and subjective well-being (SWB) among college students have been deemed as importantissues in studies. The present study aims to explore any influential elements of gender and age to their QOL andSWB, and to know if the QOL is influential to the SWB. Participants amounted to 651 respondents totally fromthree Indonesian universities (Diponegoro University, Padjajaran University, North Sumatra University) wereinvolved in a purposive sampling using two instruments, i.e., the Personal Wellbeing Index-Adult (PWI-A) tomeasure SWO and The World Health Organization Quality of Life-BREF (WHOQOL-BREF) to measure QOL.Ordinal Logistic Regression (OLR) test was used in the analysis. The results showed that age and gender had asignificant effect on SWB (respectively .11 & .040, with p < .05) but had no effect on QOL of students(respectively .510 & .751, with p < .05). In addition, QOL was shown to affect SWB (p < .05). As a result,counselors and stakeholders on campus are encouraged to consider age and sex factors in their attempts ofincreasing college students’ SWB. However, further research is still suggestible to explore more complex factorsin college students’ QOL, which can include social, individual, and other demographic factors.